2003
DOI: 10.1074/jbc.m212474200
|View full text |Cite
|
Sign up to set email alerts
|

Adenine Release Is Fast in MutY-catalyzed Hydrolysis of G:A and 8-Oxo-G:A DNA Mismatches

Abstract: MutY, a DNA repair enzyme, is unusual in that it binds exceedingly tightly to its products after the chemical steps of catalysis. Until now it was not known whether the product being released in the rate-limiting step was DNA, adenine, or both. ؊1 . This was much faster than the rate-limiting step, at 0.006 -0.015 min ؊1 . Gel retardation experiments showed that AP-DNA release was very slow, consistent with it being the rate-limiting step. Thus, the kinetic mechanism involves fast adenine release after hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 28 publications
6
31
0
1
Order By: Relevance
“…17 The rate constant k 3 measured for the reaction of MutY with the OG:Z3 substrate was essentially identical to that measured with the OG:A substrate under all conditions. This is not unexpected since k 3 is dominated by release of MutY from the DNA product, 20 which is the same for both substrates after base excision and release.…”
Section: Glycosylase Activity Of Muty With Modified Substratesmentioning
confidence: 84%
See 2 more Smart Citations
“…17 The rate constant k 3 measured for the reaction of MutY with the OG:Z3 substrate was essentially identical to that measured with the OG:A substrate under all conditions. This is not unexpected since k 3 is dominated by release of MutY from the DNA product, 20 which is the same for both substrates after base excision and release.…”
Section: Glycosylase Activity Of Muty With Modified Substratesmentioning
confidence: 84%
“…[17][18][19] Pre-steady state experiments revealed that MutY has a high affinity for the product such that release of the DNA product is rate-limiting. 17,19,20 Moreover, the identity of the base opposite A greatly affects both the rate of product release as well as the intrinsic rate of adenine removal determined under single-turnover conditions. 17 Product release is likely enhanced in vivo by interactions with other BER enzymes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] For hTDG, the resulting product inhibition is so potent that it exhibits almost no turnover in vitro. We therefore used single turnover kinetics and saturating enzyme conditions to obtain rate constants (k max ) that were not impacted by product release or the bimolecular association of enzyme and substrate, and thus correspond to the maximal catalytic activity of hTDG ( Figure 3).…”
Section: Single Turnover Kineticsmentioning
confidence: 99%
“…Release of the base (B) likely precedes very slow release of AP DNA (apD). 36,38 The k max values report on the reaction steps from the initial hTDG·DNA collision complex to the ternary product complex. Electrostatic potential maps of the 5-substituted uracil and cytosine bases used in this work.…”
Section: Supplementary Materialsmentioning
confidence: 99%